Cleidocranial Dysplasia of a 13-year-old Bangladeshi Girl: A Rare Case Report - Rita, Sufia Nasrin; Hasan, Muhammad Mahdee; Amin, Nurul; Sadat, SM Anwar (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Cleidocranial dysplasia (CCD) is an uncommon autosomal inheritant congenital skeletal defect that primarily affects the bones and teeth, and shows an autosomal inheritance. A 13-year-old Bangladeshi girl presented with delayed eruption of the permanent anterior teeth. She was short-statured, well-oriented young girl with narrow, drooped shoulders, malformed or absent clavicles, brachycephalic head with frontal and parietal bossing, hypoplasticzygomatic bones, bulging calvarium, and depressed nasal bridge with a broad alar base. Intraoral examination revealed persistence of the primary dentition, delayed eruption of the permanent teeth, an Angle class III malocclusion, negative overjet, bilateral posterior crossbite. This rarecase of CCD is so far the first case from Bangladesh to be documented in perspective to dental surgery and orthodontics. J Bangladesh Coll Phys Surg 2020; 38(4): 213-217